The Authority of the Constitutional Court in Reviewing International Agreements : Case of ASEAN Charter Review - Putri, Putu Pipit Pricellia Eka; Lue, Elisabeth; Atalo, Rainhard Florian (IJBLE Scientific Publications Community Inc., 2024)
This study discusses the authority of the Constitutional Court of the Republic of Indonesia in reviewing international agreements, focusing on the ASEAN Charter case. The results of the study indicate that the Constitutional Court does not have the authority to review international agreements, because its duties are limited to reviewing laws against the Constitution. Therefore, the Constitutional Court's decision to review laws related to the ASEAN Charter is considered inconsistent with applicable legal provisions. The implications of this review on Indonesia's position in ASEAN are not significant, because the Constitutional Court's decision is more aimed at harmonizing national law with Indonesia's international obligations. This study emphasizes the importance of a clear understanding of the limitations of the Constitutional Court's authority in the context of international law and its impact on Indonesia's relations in ASEAN.